ADVANCED ADIPOSE PROTEIN EXTRACT PROMOTES LIMBAL STEM CELLS REGENERATION THROUGH STEM CELL NICHE MODULATION: Oral Presentation - Experimental Study - Ophthalmologist - YUYUN RINDIASTUTI (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Limbal stem cells (LSCs) play important role in maintaining corneal clarity. Disruption of LSCs or its niche may lead to LSCs deficiency that result in blindness. This study aimed to investigate therapeutic effect of advanced adipose protein extract (AAPE) in LSCs regeneration. Methods : AAPE was derived from adipose derived mesenchymal stem cell secretome purifed by ultrafiltration technique. 2D culture of LSCs were exposed by 0.25 NaOH, then treated with serum-free media as control group, media supplemented with 20% and 50% AAPE as treatment group I and II, respectively. MTT assay was conducted to measure cell proliferation and in vitro scratch assay to assess cell migration at 48 hours after treatment. EGF, FGF, HGF, and KGF from supernatant were measured by ELISA. Data was analyzed using One way ANOVA and post-hoc Tukey. Results : A 50% AAPE successfully promoted the highest proliferation and migration rate of LSCs compared to control group (94.38±2.51%, P 0.001; 68.52±3.51%, P 0.001). EGF (1216.67pg/mL), FGF (988.25pg/mL), HGF (119.33pg/mL), and KGF (793.25pg/mL) from 50% AAPE supernatant group were highest among other groups. Conclusion : A 50% AAPE demonstrated optimal beneficial effect on LSCs regeneration through upregulation of EGF, FGF, HGF, and KGF associated with niche modulation.